Antiangiogenic therapy in breast cancer - Stelmaszuk, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2007)
In recent years, antiangiogenic therapy has demonstrated significant activity in patients with metastatic breast cancer. Definition of the mechanism of action of anti-VEGF treatment, the primary mediator of angiogenesis, enables this phenomenon to be implemented in clinical practice. Bevacizumab monoclonal antibody is targeted against vascular endothelial growth factor, and plays a central role in antiangiogenic treatment of tumours. The initial randomized phase III trial of bevacizumab with capecitabine in patients with metastatic breast cancer did not improve progression-free survival. However, in the Eastern Cooperative Oncology Group 2100 trial of patients with previously untreated metastatic breast cancer, bevacizumab combined with paclitaxel doubled progression-free survival. Based on these encouraging findings, current studies are designed in adjuvant setting primary breast cancer. Tyrosine kinase inhibitors have shown antiangiogenic activity in breast cancer. Now these oral drugs are being investigated in every stage of breast cancer. Combination therapy consisting of standard chemotherapy with a brand-new molecular regimen for regulated angiogenesis creates hopes of improving treatment options for these patients. But research is ongoing to define prediction factors and describe chances to monitor response to antiangiogenic drugs. The treatment time is still indefinite.